Statistical Assessment of the Development of Small and Medium-Sized Businesses in the Republic of Kazakhstan - V. ZARUBINA; M. ZARUBIN; D. KENZHEBEKOVA; A. KURMANGALIEVA; YE. VASSILCHUK (Communications of International Proceedings, 2020)
The purpose of this research article is to develop a methodological approach to determining the integral rating of business development in the regions of Kazakhstan on the basis of the proposed indicators, the forecast of business development. Methodology – statistical methods were used in the preparation of the article, such as the use of the geometric mean to determine the rating of regions, trend analysis, and the rating method was used as a mathematical model. The result (value) of this work is to conduct a statistical analysis and substantiate the possibility of using the proposed integral index as a tool for assessing the development of the level of entrepreneurship in the regions. Conclusions – methods of statistical analysis, namely on the basis of calculating the integral index, are applicable to assess the development of entrepreneurship in the regions of the country, to form a rating based on the geometric mean.
Keywords: Small and Medium-Sized Businesses; Rating; Index; Integral Index; Assessment of Business Development.